Private Damages Actions in EU Competition Law and Restorative Justice: Towards a New Streamlined Institutional Framework? - Pieter Van Cleynenbreugel (Market and Competition Law Review)
The transposition of Directive 2014/104 on private damages actions marks an important development in the setting up of a harmonised private competition law enforcement regime across different EU Member States. Coupled with deterrence-focused public enforcement, the European Union has taken a necessary and welcomed step towards enhancing justice for all those individuals and competitors damaged by competition law infringements. This article argues, however, that the current emphasis on balancing public and private enforcement of the European Commission focuses too little on the need and healing effects of restoration. At the same time, the Directive contains a promising restorative justice opening by virtue of its Article 18. Starting from that opening, the article will propose a more developed way forward, taking the form of the setup and development of so-called antitrust “trust funds”. Exploring the legal possibilities and limits of such funds, the article questions to what extent this approach could be a useful complementary way to overcome the limits identified. It will be submitted that, although it is legally possible to set up those trust funds under EU law, important practical questions have to be addressed prior to doing so. Having outlined the potential features and limits of this approach, the article additionally calls for more and comparative research to be performed in this area.